Does the frequency of reminders matter for their effectiveness? A randomized controlled trial - Armenak Antinyan; Zareh Asatryan; Zhixin Dai; Kezhi Wang (Cardiff University, Cardiff Business School, 2021)
We assess the impact of reminder frequency on the probability of paying overdue property taxes in a randomized controlled trial in China. One reminder a week (sent as a text message) considerably increases the probability of tax compliance and results in tangible fiscal gains compared to a one-off reminder. However, increasing the frequency of reminders to two text messages a week diminishes their effectiveness. The takeaway of our study is that frequent reminders are an important trigger for human behavior, nonetheless, beyond a certain frequency the effectiveness of additional reminders seems to decline.
Keywords: C93; H24; H26; 330; Reminder Frequency; Randomized Controlled Trial; Tax Compliance